Penetrating Orbitofrontal Foreign Body: Case Report - Bhide, Anuj; Velho, Vernon; Jain, Nimesh; Bhople, Laxmikant (Indian Journal of Neurotrauma, 2018)
Orbitofrontal foreign-body injuries comprise a major cause of all facial injuries referred to a neurosurgeon. The authors hereby present an unusual case of a pressure regulator of a domestic pressure cooker impacted into the orbit and extending through the orbital roof into the basifrontal cortex. The globe was intact externally with no obvious sign of such a large object impacted behind the globe. On imaging, the foreign body was found to have fractured the orbital roof with one end protruding into the basifrontal cortex. A transcranial approach was taken to remove the object with removal of the orbital rim and roof to reach the object. After successful retrieval of the metallic body, all displaced bone fragments were removed and the dural closure was done in a watertight manner. The vision could not be salvaged, most likely due to damage to the optic nerve. However, the globe was left intact and the ocular movements were normal. An important factor to consider in removal of such foreign bodies is that the bone fragments that get impacted should be meticulously removed and the dural tears should be sealed to prevent any intracranial infections and cerebrospinal fluid leaks. Removal of the orbital rim helps in adequate exposure of the retro-orbital space and the basifrontal dura.
Keywords: pressure cooker; foreign body; orbitofrontal; pressure regulator